2014
DOI: 10.1111/idj.12121
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental caries activity, quality of life and obesity in Brazilian adolescents

Abstract: Obesity, dental caries and quality of life were not correlated. Adolescents with normal weight presented a low perception of the impact of oral conditions on quality of life; however, it seemed to affect psychological aspects in their daily performances. Providing adolescents with nutritional assistance may prevent obesity and dental caries, and improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 24 publications
(28 reference statements)
4
28
0
5
Order By: Relevance
“…The results showed a significant effect of BMI on children's dmft, with an inverse relationship between these two variables, consistent with the results of different studies carried out [7, 12, 18–20]. In contrast, some researchers have reported a direct relationship between BMI and dmft [11, 13, 21–25].…”
Section: Discussionsupporting
confidence: 89%
“…The results showed a significant effect of BMI on children's dmft, with an inverse relationship between these two variables, consistent with the results of different studies carried out [7, 12, 18–20]. In contrast, some researchers have reported a direct relationship between BMI and dmft [11, 13, 21–25].…”
Section: Discussionsupporting
confidence: 89%
“…This study has demonstrated that any such analysis must include data about sugar and carbohydrate consumption. Similar results were observed in Brazilian adolescents and Korean adults.…”
Section: Discussionsupporting
confidence: 88%
“…The result of the association between oral clinical conditions and OHRQoL is consistent with previous research in children, adolescents and adults. For example, Foster Page reported a direct relationship between malocclusion and poor OHRQoL in adolescents, and that OHRQoL was indirectly predicted by dental caries experience.…”
Section: Discussionsupporting
confidence: 88%